Changes in wheat growth, development, and yield when herbicides are applied - S.Kh. Sullieva (Zien Journals, 2021)
In this article, Puma super (1 l / ha), Granstar (15 g / ha) was applied against cereal weeds, and as a result of elimination, the Kroshka variety of winter wheat had a long stalk, a large number of grains in the stalks, and a large number of grains in the stalks. an increase in grain yield from a single spike, which has been reported to radically improve the grain structure of Puma super (1 l / ha) and Granstar (15 g / ha) herbicides against double-stranded weeds when mixed and thawed
Keywords: Herbicide; Granstar Herbicide; Puma Super Herbicide; Winter Wheat